(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We have defined and evaluated total eccentricity indices of polyhex nanotubes TUAC6(p, q) and TUZC6(p, q). In thispaper, we compute First Total Eccentricity Index, Second Total Eccentricity Index, First Multiplicative Total Eccentricity Index, Second Multiplicative Total Eccentricity Index, First Hyper Total Eccentricity Index, Second Hyper Total Eccentricity Index, First Multiplicative Hyper Total Eccentricity Index and Second Multiplicative Hyper Total Eccentricity Index of a graph using Total graph of a graph. We evaluate the value of these indices for some standard graphs.